2014
DOI: 10.1037/a0036700
|View full text |Cite
|
Sign up to set email alerts
|

Examining the associations of racism, sexism, and stressful life events on psychological distress among African-American women.

Abstract: African American women may be susceptible to stressful events and adverse health outcomes as a result of their distinct social location at the intersection of gender and race. Here, racism and sexism are examined concurrently using survey data from 204 African American women residing in a southeastern U.S. urban city. Associations between racism, sexism, and stressful events across social roles and contexts (i.e., social network loss, motherhood and childbirth, employment and finances, personal illness and inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
63
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 32 publications
(59 reference statements)
3
63
0
2
Order By: Relevance
“…Similarly, results from Piña-Watson et al’s [97] study of Mexican high school students suggest that gender moderates the relationship between discrimination stress and well-being, with female adolescents experiencing higher levels of somatic symptoms, depressive affect, suicidal ideation, and discrimination stress than their male counterparts. Studies of Asian American, Latina, and African American women have explored how they are exposed to discrimination based on at least two of their social identities (i.e., race and gender), which may negatively influence their mental health outcomes, such as stress [98] and PTSD [99]. Stevens-Watkins et al [98] insist that it is problematic to exclude the constructs of racism and sexism from the measurement of stressful life events, since they are correlated with one another and with stressful life events.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, results from Piña-Watson et al’s [97] study of Mexican high school students suggest that gender moderates the relationship between discrimination stress and well-being, with female adolescents experiencing higher levels of somatic symptoms, depressive affect, suicidal ideation, and discrimination stress than their male counterparts. Studies of Asian American, Latina, and African American women have explored how they are exposed to discrimination based on at least two of their social identities (i.e., race and gender), which may negatively influence their mental health outcomes, such as stress [98] and PTSD [99]. Stevens-Watkins et al [98] insist that it is problematic to exclude the constructs of racism and sexism from the measurement of stressful life events, since they are correlated with one another and with stressful life events.…”
Section: Resultsmentioning
confidence: 99%
“…Studies of Asian American, Latina, and African American women have explored how they are exposed to discrimination based on at least two of their social identities (i.e., race and gender), which may negatively influence their mental health outcomes, such as stress [98] and PTSD [99]. Stevens-Watkins et al [98] insist that it is problematic to exclude the constructs of racism and sexism from the measurement of stressful life events, since they are correlated with one another and with stressful life events. This highlights the importance of examining the intersectionality of social identities in mental health research, and there is a growing body of literature on this topic.…”
Section: Resultsmentioning
confidence: 99%
“…Related research in public health indicates that the interaction of racism and sexism predicted increased stress in African-American, women college students (King, 2003). Yet, other research has suggested independent, but not interactive, effects for racism or sexism predicting distress (Stevens-Watkins et al, 2014; Szymanski et al, 2010). Thus, examining interactive effects of gender and race/ethnicity on negative judgments toward PWIDs was exploratory.…”
Section: Introductionmentioning
confidence: 91%
“…The insidious and pervasive effects of racism and other forms of oppression can be seen across the life course in several areas, including child birth (Dominguez, Dunkel-Schetter, Glynn, Hobel, & Sandman, 2008), parenting , intimate relationships (Cowdery et al, 2009), gender roles (Collins, 1998a(Collins, , 1998b, and racial and ethnic identity (Carter & Reynolds, 2011). In addition, such exposure to injustices contributes to existing health (Sanders-Phillips, Settles-Reaves, Walker, & Brownlow, 2009;Stevens-Watkins, Perry, Pullen, Jewell, & Oser, 2014) and economic (Becker, 2010;Darity & Mason, 2004) disparities.…”
Section: Stress Modelmentioning
confidence: 99%